The Effect Of Adding Chayote Puree To The Quality Of Chicken Dumpling - Adriana, Ghina; Gusnita, Wiwik (Universitas Negeri Padang, 2023)
This research was motivated by the use of chayote puree to vary the chicken dumplings which aims to utilize local food ingredients and increase the variety of dumpling products. The addition of chayote puree aims to increase the elasticity of the chicken dumplings by analyzing the effect of the addition of chayote puree as much as 15%, 25%, 35% on the quality of the dumplings in terms of organoleptic. . This type of research is a pure experiment with Completely Randomized Design (CRD) method. The data used is primary data obtained directly from 3 expert panelists who provide answers to a questionnaire (organoleptic test format) about the quality of chicken dumplings with the addition of chayote puree. The data that has been obtained is then tabulated in tabular form and an analysis of variance (ANOVA) is performed. If the analysis of variance shows Fcount > Ftable, then Duncan's test is performed. The results showed that the addition of chayote puree had a significant effect between 15%, 25%, 35% on the quality of the dumplings, namely the quality of the chewy texture and the taste of the chayote. The quality of the shape (neat and uniform), the yellowish-white color and the distinctive aroma of the chicken did not affect the quality of the chicken dumplings. The results of the quality test of chicken dumplings with the addition of chayote puree were the best in the X3 treatment with the addition of 35% chayote puree.